A new "caliphate" in the Middle East : is there an Abu Sayyaf-ISIS link? - Joseph, Franco (2014)
A video of a purported member of the Abu Sayyaf Group (ASG) pledging support to the Islamic State of Iraq and al-Sham (ISIS) surfaced recently. With an apparent spike in ASG-related activities, this is interpreted as evidence of convergence between the groups, However, the localised factors that motivate ASG factions should not be ignored.